STRATEGI PEMERINTAH DESA CIWARINGIN DALAM MENGATASI JUDI ONLINE DI KALANGAN MASYARAKAT - Annisa Aisatul Maryam Prabowo; Indra Aditya; Kariena Febriantin (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the strategies implemented by the Village Government of Ciwaringin to tackle the widespread issue of online gambling among its residents. The prevalence of online gambling has caused various negative impacts, including financial losses, mental health issues, and social problems. The study employs a qualitative case study method using Geoff Mulgan’s (2009) strategy theory framework, which includes five aspects: purpose, environment, direction, action, and learning. Data were collected through interviews with the village head, academics, and online gambling perpetrators, as well as through observation and documentation. The findings reveal that the village government undertook strategic efforts such as education, awareness campaigns, community empowerment, and collaboration with community leaders and institutions. These strategies have proven effective in reducing the number of online gambling participants over the years. The study concludes that active involvement of the village government is crucial in mitigating the negative impacts of online gambling and in fostering a law-abiding and empowered community